Bio-Fabrication of Silver Nanoparticles Using Catha edulis Extract: Procedure Optimization and Antimicrobial Efficacy Encountering Antibiotic-Resistant Pathogens - Numan, Abdulqawi A.; Ahmed, Mashhour; Galil, Mansour S. A.; Al-Qubati, Mohyeddine; Raweh, Ayman A.; Helmi, Enas A. (Scientific Research Publishing, 2022)
The current study aimed to optimize a green synthesis procedure for fabricating biogenic silver nanoparticles (AgNPs) using an aqueous extract of Catha edulis (Qat; khat) leaves. The final product was characterized using various analytical techniques. Parameters optimization including pH, contact time, temperature, and amount of leaf extract were carried out. AgNPs formation was confirmed by UV-vis spectra at 403 nm, FT-IR, and XRD peaks. FTIR spectra showed the presence of various biochemical metabolites which played a critical role in the bio-reduction, capping, and stabilization of AgNPs. The biogenic AgNPs were spherical in shape with an average size between 27 and 32 nm as estimated from XRD and SEM images. Biogenic AgNPs showed significant activities against sensitive and multi-drug resistance Escherichia coli and Staphylococcus aureus strains. In addition, the experimental results proved that AgNPs have higher efficacy than antifungal drugs that are commonly used to treat Candida albicans oral infections.